A Robotic Therapy Case Study: Developing Joint Attention Skills With a Student on the Autism Spectrum. (September 2017) - Charron, Nancy; Lewis, Lundy; Craig, Michael
The purpose of this article is to describe a possible methodology for developing joint attention skills in students with autism spectrum disorder. Co-robot therapy with the humanoid robot NAO was used to foster a student's joint attention skill development; 20-min sessions conducted once weekly during the school year were video recorded and analyzed for joint attention. Robot therapy may be a viable method to improve communication skills in individuals identified with autism spectrum disorder. This particular student was clearly motivated by working with a humanoid robot.